A low-smoke halogen-free flame-retardant crosslinked polyolefin insulated cable and a preparation method thereof
Patent Information
- Application Number
- CN202611219908.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-09
AI Technical Summary
1.PVC绝缘电缆:燃烧释放大量氯化氢腐蚀性剧毒烟气,火灾中极易造成人员窒息、精密设备腐蚀报废,卤素环保指标不达标,已被多数重点工程限制使用;
1.该低烟无卤阻燃交联聚烯烃绝缘电缆及其制备方法,采用超细氢氧化铝、纳米氢氧化镁、硼酸锌、可膨胀石墨、三聚氰胺氰尿酸盐五元复配三相阻燃填料,构建液相吸热、气相抑烟、固相成炭协同阻燃体系,搭配中空蜂窝发泡填充层阻断热量向内传导,成品可达GB/T31247A级最高阻燃等级;燃烧烟气透光率≥78%,卤素总含量低于0.05%,燃烧无氯化氢等腐蚀性有毒烟气释放,烟气毒性t0级,火灾时可减少人员窒息、设备腐蚀损毁风险,适配医院、隧道、高层建筑等高消防要求密闭场景。
Smart Images

Figure CN122889513A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of power transmission cable technology, specifically to a low-smoke, halogen-free, flame-retardant cross-linked polyolefin insulated cable and its preparation method. Background Technology
[0002] Currently, mainstream cables on the market are divided into three categories: polyvinyl chloride (PVC) cables, ordinary cross-linked polyethylene (XLPE) cables, and conventional low-smoke halogen-free cables. Each category has its own technical shortcomings that make them difficult to integrate. 1. PVC insulated cables: When burned, they release a large amount of corrosive and highly toxic hydrogen chloride fumes, which can easily cause asphyxiation and corrosion damage to precision equipment in a fire. They also fail to meet halogen environmental protection standards and have been restricted from use in most key projects. 2. Ordinary cross-linked polyethylene cable: It does not contain a flame-retardant modification system, spreads flame rapidly under open flame, has a high smoke density, has no smoke-suppressing components, and has a fire protection rating of only C, which cannot meet the mandatory A-level flame-retardant standard for enclosed tunnels, hospitals, etc. 3. Traditional low-smoke halogen-free cables: To achieve flame retardancy, a large amount of inorganic powders such as aluminum hydroxide and magnesium hydroxide are used, which has ten inherent defects: ① The inorganic filler has poor compatibility with the polyolefin substrate, and extrusion molding is prone to producing pores, pitting, and broken strips, resulting in a high scrap rate; ② The crosslinking system is singular, relying only on single silane grafting, resulting in uneven crosslinking distribution, insufficient crosslinking degree at the conductor edges, and insulation cracking after long-term thermal aging; ③ There is no bonding modification at the interface between the insulation layer and the conductor, filler layer, and inner lining layer, resulting in multi-layer structure delamination and water ingress breakdown after high and low temperature cycling and water immersion; ④ The flame retardant system relies only on the dehydration and heat absorption of single hydroxides, without a synergistic mechanism of gas-phase flame retardancy and char formation flame retardancy, and the char layer is prone to falling off under high-temperature open flame, resulting in insufficient flame retardancy. ⑤ Short service life; ⑥ The conductor lacks moisture-proof and anti-oxidation pretreatment, and the copper conductor will oxidize to form copper oxide when exposed to moisture for a long time, which increases the contact resistance and reduces the current carrying capacity; ⑦ The cable filling only uses ordinary solid flame-retardant strips without heat insulation and buffer structure, and the heat will be quickly conducted inward during combustion, burning the insulation; ⑧ The shielding layer is only a single layer of copper strip, which is not effective in electromagnetic shielding and interferes with the weak current control system when operating at high current; ⑨ The armor has no buffer isolation, and the sharp corners of the steel strip scratch the inner lining and insulation; ⑨ The manufacturing process uses steam cross-linking, which requires large equipment investment, consumes a lot of energy, and the cross-linking time is uncontrollable, resulting in large dispersion of the finished product performance; ⑩ The overall resistance of the cable to rodents and insects, acid and alkali, and low temperature brittleness is insufficient, and the service life is greatly shortened when buried underground or in the cold northern environment. Summary of the Invention
[0003] The purpose of this invention is to provide a low-smoke, halogen-free, flame-retardant cross-linked polyolefin insulated cable and its preparation method, so as to solve the problems mentioned in the background art.
[0004] To achieve the above objectives, the present invention provides the following technical solution: a low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable, wherein the cable as a whole has a coaxial layered composite structure from the inside to the outside, comprising: a pretreated tin-plated copper conductive core wire, a double-layer co-extruded composite cross-linked polyolefin insulation layer, a hollow foamed gradient flame-retardant filling layer, a composite shielding layer, a low-smoke halogen-free flame-retardant inner lining layer, an anti-corrosion buffer isolation non-woven fabric, a galvanized steel tape armored protective layer, and a rodent-repellent, weather-resistant, low-smoke halogen-free outer sheath layer.
[0005] 1. Pre-treated tin-plated copper conductive core wire Multiple strands of oxygen-free copper monofilaments are tightly twisted together, and the surface of the monofilaments is hot-dip tin-plated for oxidation resistance. The stranded conductors are completely dried with 55°C hot air to remove surface moisture. The outer surface of the conductor is uniformly sprayed with a **silane coupling agent + nano tin dioxide anti-oxidation composite coating**, with a coating thickness of 5~12μm. Nano tin dioxide uniformly fills the stranded gaps of the conductors, preventing copper from contacting moisture and oxygen for oxidation. One end of the silane coupling agent binds to the hydroxyl groups of the copper conductor, and the other end is linked to the outer insulating polyolefin molecules, achieving seamless bonding between the conductor and the insulation layer, eliminating delamination gaps under operation, immersion, and temperature changes.
[0006] Conductor cross-section specifications: 1.5~300mm 2 A single cable consists of 2 to 5 independently insulated core wires.
[0007] 2. Double-layer co-extruded composite cross-linked polyolefin insulation layer It adopts a double-layer co-extrusion molding process, with the inner layer being a thin adhesive transition layer and the outer layer being the main flame-retardant cross-linked insulating layer. The two layers are extruded simultaneously without a secondary bonding process.
[0008] (1) Weight ratio of raw materials for the outer main cross-linked polyolefin insulation layer: Ethylene-vinyl acetate copolymer (EVA) 35-45 parts, linear low-density polyethylene (LLDPE) 20-28 parts, metallocene polyethylene (mPE) 8-12 parts (ternary composite matrix), silane crosslinking agent 2.2-3.5 parts, organotin crosslinking catalyst 0.3-0.8 parts, elastic core-shell compatibility toughening agent 5-7 parts, three-phase composite flame retardant filler 40-55 parts, nano boron nitride thermally conductive powder 1.0-2.5 parts, composite antioxidant 1.2-2.0 parts, composite lubrication processing aid 1.0-1.8 parts; Elastic core-shell compatibility toughening agent: polyacrylate core-polyethylene shell core-shell particles, with a particle size of 200~400nm, coat the surface of inorganic flame retardant powder, solve the problems of agglomeration of highly filled powder and poor compatibility with substrate, and the extruded surface is free of pores and pits. Three-phase composite flame-retardant filler: ultrafine aluminum hydroxide, nano magnesium hydroxide, zinc borate, expandable graphite, and melamine cyanurate are mixed in a mass ratio of 5:2:1:1:1 to form a three-phase synergistic flame-retardant system of liquid phase dehydration and heat absorption, gas phase inert gas smoke suppression, and solid phase expansion into char. Nano-boron nitride thermally conductive powder: uniformly dispersed within an insulating substrate, constructing a continuous nano-thermal conductive network, increasing the insulation thermal conductivity by 45%, reducing conductor operating temperature rise by 8~12℃, and increasing the current flow rate of the same cross-section by 10%; (2) Inner bonding transition layer: EVA grafted with maleic anhydride substrate, thickness 0.15~0.3mm, synchronously melt-extruded with the outer insulation layer, the two molecular chains interpenetrate and entangle with each other, integrally formed without interface separation (innovation point 5). The total thickness of the insulation layer is 0.8~2.6mm, the degree of cross-linking is ≥88%, the long-term allowable working temperature is 90℃, and there is no crack when bent at a low temperature of -40℃.
[0009] 3. Hollow foam gradient flame-retardant filler layer Multiple insulated core wires are continuously extruded with honeycomb hollow foam flame-retardant filler strips at the gaps in the cable. The foaming ratio is 2.5 to 3.5 times, and the filler strips contain uniformly distributed hollow honeycomb pores with a diameter of 0.3 to 0.8 mm. The hollow structure forms a static heat-insulating air layer, which significantly blocks the conduction of external heat to the inside of the cable core during fire, delaying insulation burn-out failure. At the same time, the hollow foam has high elasticity, buffering stress when the cable is repeatedly bent and squeezed, preventing the insulation layer from being crushed and damaged. The filler strip substrate and the insulation layer are made of the same polyolefin material, with excellent interfacial compatibility.
[0010] 4. Composite shielding layer After the cable core is filled, a double-layer copper tape staggered wrapping shielding layer is set on the outside. The overlap seams of the two copper tapes are staggered, and the overlap rate of the single copper tape wrapping is ≥28%. A graphite conductive buffer composite tape is simultaneously wrapped longitudinally on the outside of the double copper tape. The double-layer staggered copper strip ensures no shielding gaps around the entire circumference, with an electromagnetic shielding effectiveness of ≥60dB in the 30MHz~1GHz frequency band, eliminating high-current electromagnetic interference; the graphite composite strip also has the functions of auxiliary heat dissipation, buffering and shock absorption, absorbing the extrusion stress of the armor, and simultaneously dissipating the heat of the cable core during operation.
[0011] 5. Low-smoke halogen-free flame-retardant inner lining The outer side of the shielding layer is a thin extruded low-smoke halogen-free polyolefin liner with a thickness of 0.4~0.8mm. It isolates the metal armor from direct contact with the shielding layer and provides basic waterproofing, flame retardant cushioning.
[0012] 6. Corrosion-resistant, cushioning, and insulating non-woven fabric The outer side of the inner lining is continuously wrapped with a double-sided self-lubricating and anti-corrosion non-woven fabric isolation layer, and both sides of the non-woven fabric are impregnated with a silicone-based lubricating and anti-corrosion coating. When the steel strip armor is wrapped subsequently, the lubricating coating prevents the sharp corners of the steel strip from puncturing or scratching the inner lining and insulation structure. The anti-corrosion coating isolates the galvanized steel strip from water vapor and acid and alkali ions from groundwater, thus delaying the corrosion failure of the steel strip.
[0013] 7. Galvanized steel strip armored protective layer The outer side of the isolation non-woven fabric is wrapped with 0.2~0.5mm galvanized steel strips with a gap of ≥3mm, which improves the cable's resistance to underground extrusion, gravel impact, and rodent and insect damage.
[0014] 8. Rodent-repellent, ant-resistant, weather-resistant, low-smoke, halogen-free outer sheath. The outer side of the armor is extruded with a high weather-resistant, low-smoke, halogen-free flame-retardant outer sheath, with a thickness of 1.5~3.2mm; the sheath base material is compounded with 0.8~1.5 parts of natural peppermint, capsaicin, camphor compound plant repellent extracts, free of heavy metals and toxic repellent agents, providing long-lasting repellency against rats and termites; at the same time, ultraviolet light stabilizer masterbatch and acid and alkali resistant modifier are added, increasing the weather resistance life of outdoor direct burial and cable tray laying by 60%; the combustion smoke density rating is s1, the toxicity rating is t0, and there is no halogen corrosive gas emission.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This low-smoke, halogen-free, flame-retardant cross-linked polyolefin insulated cable and its preparation method utilize a five-component compound three-phase flame-retardant filler consisting of ultrafine aluminum hydroxide, nano magnesium hydroxide, zinc borate, expandable graphite, and melamine cyanurate. This filler constructs a synergistic flame-retardant system with liquid-phase heat absorption, gas-phase smoke suppression, and solid-phase char formation. Combined with a hollow honeycomb foam filling layer to block heat conduction inward, the finished product achieves the highest flame-retardant rating of GB / T31247A. The light transmittance of the combustion smoke is ≥78%, the total halogen content is less than 0.05%, and no corrosive or toxic smoke such as hydrogen chloride is released during combustion. The smoke toxicity is t0 level, which can reduce the risk of personnel asphyxiation and equipment corrosion damage in the event of a fire. It is suitable for enclosed scenarios with high fire protection requirements, such as hospitals, tunnels, and high-rise buildings.
[0016] 2. The low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable and its preparation method involve spraying a silane coupling agent + nano tin dioxide composite coating onto the conductor. This not only blocks the oxidation of the copper conductor and reduces current carrying loss, but also achieves seamless bonding between the conductor and the insulation layer, preventing delamination breakdown after high and low temperature cycling and water immersion. It also constructs a continuous heat conduction network, which reduces the temperature rise of the conductor during operation and increases the current carrying capacity of the same cross-section.
[0017] 3. This low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable and its preparation method utilize a composite shielding structure formed by double-layer staggered overlapping copper tape and an outer graphite conductive buffer composite tape. High-current operation does not interfere with weak current control systems, and the graphite layer synchronously assists in heat dissipation and stress buffering. The galvanized steel tape armor, combined with double-sided silicon-based anti-corrosion and lubricating non-woven fabric isolation, prevents the steel tape from scratching the insulation, delays armor corrosion, and provides strong resistance to pressure and impact. 4. The low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable and its preparation method utilize polyacrylate core-polyethylene shell nano-toughening agent in the insulation material, which greatly improves the compatibility between high-filled inorganic flame-retardant powder and polyolefin substrate. The extrusion process is free of air holes and pitting. The segmented warm water pre-crosslinking + deep water secondary curing process replaces the traditional steam crosslinking process, resulting in less equipment investment, lower energy consumption, uniform and controllable crosslinking degree, small performance dispersion of finished product, and significant advantages for large-scale production. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram of the structure of the low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable of the present invention; Figure 2 This is a flowchart of the preparation method of the low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable of the present invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0022] Please see Figures 1-2 The present invention provides a technical solution: a low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable, which is coaxially arranged from the inside to the outside as follows: a pre-treated tin-plated copper conductive core wire, a double-layer co-extruded composite cross-linked polyolefin insulation layer, a hollow foamed gradient flame-retardant filling layer, a composite shielding layer, a low-smoke halogen-free flame-retardant inner lining layer, a corrosion-resistant buffer isolation non-woven fabric, a galvanized steel tape armored protective layer, and a rodent-repellent, weather-resistant, low-smoke halogen-free outer sheath layer; The surface of the pretreated tin-plated copper conductive core wire is sprayed with a silane coupling agent + nano tin dioxide anti-oxidation composite coating; the double-layer co-extruded composite cross-linked polyolefin insulation layer includes an inner bonding transition layer and an outer flame-retardant cross-linked insulation layer integrally extruded; the raw materials of the outer flame-retardant cross-linked insulation layer include, by weight: 35-45 parts of ethylene-vinyl acetate copolymer, 20-28 parts of linear low-density polyethylene, 8-12 parts of metallocene polyethylene, 2.2-3.5 parts of silane cross-linking agent, 0.3-0.8 parts of organotin cross-linking catalyst, 5-7 parts of elastic core-shell compatibility toughening agent, 40-55 parts of three-phase compound flame-retardant filler, 1.0-2.5 parts of nano boron nitride thermally conductive powder, 1.2-2.0 parts of composite antioxidant, and 1.0-1.8 parts of composite lubrication processing aid; The three-phase composite flame-retardant filler is composed of ultrafine aluminum hydroxide, nano magnesium hydroxide, zinc borate, expandable graphite, and melamine cyanurate in a mass ratio of 5:2:1:1:1. The hollow foamed gradient flame-retardant filling layer is a cross-linked polyolefin foam strip with through-hole honeycomb; the composite shielding layer is a double-layer staggered copper strip with a graphite conductive buffer composite strip wrapped longitudinally on the outside; the anti-corrosion buffer isolation non-woven fabric is a double-sided impregnated silicone-based lubricating anti-corrosion coating non-woven fabric; the rodent-repellent, ant-repellent, weather-resistant, low-smoke, halogen-free outer sheath is internally compounded with natural peppermint, capsaicin, camphor, and compounded plant repellent extracts.
[0023] Example 1: 3-core 10mm 2 Low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cables for civil buildings 1.1 Cable structure design and parameter setting The cable in this embodiment is suitable for power distribution systems in densely populated civil buildings such as high-rise residential buildings and commercial complexes. It adopts a 3-core structure, which balances power supply stability and fire safety. The structural parameters of each layer are strictly matched to the innovative points of this invention, as detailed below: (1) Pre-treated tin-plated copper conductive core wire: oxygen-free copper monofilament with a purity ≥99.99% is selected, with a monofilament diameter of 0.41mm. 19 strands of monofilament are tightly twisted together to form a 10mm diameter core wire. 2 The conductor is stranded with a pitch 12 times its outer diameter. After stranding, it undergoes hot-dip tin plating with a thickness of 0.8 μm to prevent oxidation of the copper conductor. The conductor is then dried with hot air at 55℃ for 30 minutes, followed by uniform spraying of a composite coating of silane coupling agent KH-550 and nano-tin dioxide with a thickness of 8 μm. After air drying for 5 minutes, it is ready for use, achieving both antioxidant and interfacial bonding effects, corresponding to innovation point 1.
[0024] (2) Double-layer co-extruded composite cross-linked polyolefin insulation layer: total thickness 1.4mm, of which the inner bonding transition layer is 0.2mm thick, using EVA grafted with maleic anhydride with a grafting rate of 1.2% as the substrate; the outer main flame-retardant cross-linked insulation layer is 1.2mm thick, and the raw materials are precisely proportioned by weight to ensure compatibility, flame retardancy and thermal conductivity in synergy, corresponding to innovation points 2, 3, 4 and 5.
[0025] (3) Hollow foam gradient flame retardant filling layer: Low smoke halogen-free polyolefin foaming material with the same system as the insulation layer is used. It is extruded synchronously in the cable-making gap through a special foaming extruder head. The foaming ratio is 3.0 times. The diameter of the honeycomb hollow pores inside the filling strip is 0.5 mm and the pore spacing is 1.0 mm, forming a continuous heat insulation air layer, corresponding to innovation point 6.
[0026] (4) Composite shielding layer: Soft copper strip with a thickness of 0.12mm is selected, double-layer staggered wrapping, single-layer wrapping overlap rate of 30%, the two copper strip overlap seams are staggered by 180°, and there is no shielding gap; the double copper strip is wrapped with a graphite conductive buffer composite strip with a thickness of 0.1mm on the outside to achieve electromagnetic shielding and auxiliary heat dissipation function, corresponding to innovation point 7.
[0027] (5) Low smoke halogen-free flame retardant inner lining: 0.5mm thick, made of low smoke halogen-free polyolefin substrate, with a smooth surface after extrusion, free of flow marks and bubbles, serving as an isolation shielding layer and armor layer.
[0028] (6) Anti-corrosion buffer isolation non-woven fabric: 30g / ㎡ polypropylene non-woven fabric is selected, and the double sides are impregnated with a silicone-based lubricating anti-corrosion coating with a coating thickness of 2μm and a wrapping overlap rate of 15%. This avoids the sharp corners of the steel strip from scratching the inner lining layer, while isolating the armor layer from water vapor corrosion, corresponding to innovation point 8.
[0029] (7) Galvanized steel strip armored protective layer: 0.3mm thick hot-dip galvanized steel strip is selected, with zinc layer thickness ≥80g / ㎡, gap wrapping, steel strip overlap width 3.5mm, and the extrusion strength of the cable after armoring ≥15kN / m, which is suitable for underground laying and cable tray laying requirements of civil buildings.
[0030] (8) Rodent and ant repellent, weather-resistant, low-smoke, halogen-free outer sheath: 2.0mm thick, the base material is compounded with 1.2 parts of natural peppermint, capsaicin and camphor compound plant repellent extract, the mass ratio of the three is 3:2:1, and 0.5 parts of ultraviolet light stabilizer UV-531 are added to improve outdoor weather resistance and meet the use needs of civil building exterior walls, corridors and other scenarios, corresponding to innovation point 10.
[0031] 1.2 Raw material ratio (parts by weight) of the outer main flame-retardant cross-linked insulation layer Ethylene-vinyl acetate copolymer (EVA), VA content 28%, 40 parts; linear low-density polyethylene (LLDPE), melt index 2.0 g / 10 min, 24 parts; metallocene polyethylene (mPE), melt index 1.5 g / 10 min, 10 parts; silane crosslinking agent vinyltrimethoxysilane, 3.0 parts; organotin crosslinking catalyst dibutyltin dilaurate, 0.5 parts; elastic core-shell compatible toughening agent polyacrylate core-polyethylene shell, particle size 300 nm, 6 parts; three-phase compound flame retardant filler, 48 parts; nano boron nitride thermally conductive powder, particle size 50 nm, 1.8 parts; composite antioxidant composed of antioxidant 1010 and antioxidant 168 mixed in a mass ratio of 2:1, 1.6 parts; composite lubricating processing aid composed of zinc stearate and polyethylene wax mixed in a mass ratio of 1:1, 1.4 parts. The three-phase composite flame-retardant filler is composed of ultrafine aluminum hydroxide, 1μm particle size, nano magnesium hydroxide, 50nm particle size, zinc borate, expandable graphite, expansion ratio of 200 times, and melamine cyanurate (MCA) in a mass ratio of 5:2:1:1:1.
[0032] 1.3 Cable manufacturing process steps and parameter control This embodiment adopts the segmented gradient warm water pre-crosslinking plus constant temperature deep water secondary curing two-stage crosslinking process proposed in this invention to replace the traditional steam crosslinking. The specific steps are as follows, corresponding to innovation point 9.
[0033] Step 1: Conductor Pretreatment. Oxygen-free copper monofilaments are drawn into 0.41mm monofilaments using a continuous drawing machine and then fed into a hot-dip tin-plating machine for tin plating at 260℃ and a speed of 15m / min. The tin-plated monofilaments are then twisted using a compact stranding machine at a stranding speed of 8m / min. The stranded conductors are then sent into a hot air drying channel at 55℃ and a wind speed of 2m / s for 30min. After drying, the conductors are passed through an atomizing spraying device to uniformly spray a composite coating at a pressure of 0.3MPa and a spraying speed synchronized with the conductor's travel speed at 10m / min. After spraying, the conductors are allowed to air dry for 5min to ensure a firm coating adhesion.
[0034] Step 2: Mixing and granulating the insulating masterbatch. According to the above raw material ratio, all raw materials except silane crosslinking agent and organotin catalyst are put into a mixer. The mixing temperature is 140℃, the rotor speed is 60r / min, and the mixing time is 10min. During the mixing process, the ultrasonic dispersion device is turned on at a frequency of 20kHz to ultrasonically disperse the nano boron nitride, elastic core-shell compatibility toughening agent, and three-phase composite flame retardant filler to avoid powder agglomeration. After the mixing is completed, the silane crosslinking agent and organotin catalyst are added, and the mixing is continued for 2min. The molten material is fed into a twin-screw extruder. The temperature gradient of each zone of the screw is set as follows: Zone 1 120℃, Zone 2 130℃, Zone 3 135℃, Zone 4 140℃, Zone 5 145℃, and the screw speed is 80r / min. The extruded strip is cooled in a circulating water cooling tank at a water temperature of 25℃ and then fed into a pelletizer to be pelletized to a particle diameter of 3mm and a length of 4mm. After pelleting, the pellets are sent to a hot air drying chamber at a temperature of 80℃ and dried for 4h until the moisture content of the masterbatch is 75ppm. The pellets are then sealed and stored for later use.
[0035] Step 3: Double-layer co-extrusion composite insulation extrusion with segmented warm water pre-crosslinking. The dried pretreated conductor is fed into a double-layer co-extrusion extruder. The temperatures of zones one to five of the barrel are 125℃, 130℃, 135℃, 140℃, and 142℃, respectively, and the die head temperature is 142℃. The inner bonding transition layer material and the outer main insulation masterbatch are fed into two hoppers respectively and simultaneously melt-co-extruded to integrally form a double-layer composite insulation structure on the outside of the conductor. The extrusion speed is 12m / min. The extruded insulated cable semi-finished product is continuously passed through a segmented gradient warm water pre-crosslinking tank. The tank is divided into three sections with temperatures of 85℃, 90℃, and 95℃, respectively. Each section is 2m long, and the total dwell time of the cable is 60s. After pre-crosslinking, it is dried with cold air at 25℃ and then wound up for later use.
[0036] Step 4: Cable Formation and Simultaneous Extrusion of Hollow Foam Filler. Three pre-crosslinked insulated core wires are fed into the cable forming machine and twisted into a cable at a pitch of 18 times the outer diameter of the cable core, with a cable forming speed of 6 m / min. The cable forming machine integrates a foam extrusion head, simultaneously extruding hollow foam flame-retardant filler strips between the core wires. The foam extrusion head temperature is 135℃, and the foaming agent azodicarbonamide addition is 2.5%. After cable formation, a 25 g / m² polyester insulation tape is wrapped around it with a 20% overlap rate, thus finalizing the cable core structure.
[0037] Step 5: Composite Shielding and Liner Extrusion. The shaped cable core is fed into the shielding machine, where double-layer copper tape is first wrapped with staggered seams at a speed of 8 m / min. Then, a graphite conductive buffer composite tape is longitudinally wrapped with a 10% overlap. After shielding is completed, the core is fed into the lining extruder. The barrel temperature is 125℃ to 135℃, and the die head temperature is 132℃. The low-smoke halogen-free flame-retardant lining layer is extruded at a speed of 8 m / min, with the lining thickness precisely controlled at 0.5 mm.
[0038] Step 6: Wrapping and Armoring with Anti-corrosion and Buffering Non-woven Fabric. The outer side of the inner lining layer is fed into a non-woven fabric wrapping machine, where double-sided lubricated anti-corrosion and buffering non-woven fabric is wrapped at a speed of 8 m / min. After wrapping, it is fed into a steel belt armoring machine, where 0.3mm galvanized steel belts are used for gap wrapping at a speed of 6 m / min, with a steel belt overlap width of 3.5mm. After armoring, a layer of 20g / m² buffering non-woven fabric is lightly wrapped to protect the armor layer.
[0039] Step 7: Extrusion of the rodent-repellent and weather-resistant outer sheath. The armored cable core is fed into the sheath extruder. The temperatures of zones one through five of the barrel are 125℃, 130℃, 135℃, 138℃, and 140℃, respectively, and the die head temperature is 138℃. The low-smoke halogen-free outer sheath material, formulated with compound plant repellent extracts, is fed into the hopper. The extrusion speed is 8m / min, and the outer sheath thickness is controlled at 2.0mm. After extrusion, the cable enters a three-stage gradient cooling water tank. The first stage is 45℃ pre-cooling water, 3m in length; the second stage is 25℃ room temperature water cooling, 5m in length; and the third stage is 10℃ low-temperature shaping, 2m in length, to eliminate internal forming stress in the sheath and prevent later cracking.
[0040] Step 8: Constant Temperature Deep Water Secondary Curing for Deep Crosslinking. Coil the extruded sheathed cable into coils with a diameter of 1.2m and a length of 500m each. Seal the coils and immerse them completely in a 75℃ constant temperature water curing tank for 15 hours. During curing, maintain the water temperature fluctuation within ±1℃ and stir the water periodically to ensure uniform crosslinking. After curing, remove the cable and allow it to air dry naturally for 24 hours until there are no obvious water stains on the cable surface.
[0041] 1.4 Finished Product Performance Testing and Result Analysis In accordance with national standards such as GB / T31247-2014 "Classification of Combustion Performance of Cables and Optical Fibers" and GB / T12706-2020 "Extruded Insulated Power Cables and Accessories with Rated Voltage of 1kV Um=1.2kV to 35kV Um=40.5kV", the finished cables in this embodiment were subjected to comprehensive performance testing. The test items and results are as follows.
[0042] (1) Flame retardant performance: Class A flame retardant, after continuous fire supply for 30 minutes, the cable does not spread the flame or drip, and it self-extinguishes within 10 seconds after the fire is removed. The cable core insulation layer is intact and no breakdown occurs. (2) Toxic properties: The minimum light transmittance of the combustion flue gas is 79%, which meets the requirements of S1 level; the total halogen content is <0.05%, and there is no release of corrosive gases such as hydrogen chloride, and the toxicity level reaches T0 level.
[0043] (3) Insulation performance: The degree of cross-linking of the insulation layer is 89.2%. After long-term heat aging at 90℃ for 1000h, the tensile strength retention rate is 88%, and the elongation at break retention rate is 85%; the insulation resistance is ≥1.0×10 14Ω·m, dielectric strength ≥25kV / mm; (4) Mechanical properties: -40℃ low temperature bending test, bending radius is 6 times the outer diameter of the cable, bending times are 10 times, insulation layer and outer sheath have no cracks or delamination; armor layer compressive strength is 18kN / m, impact resistance is 10J impact, no damage.
[0044] (5) Other performance: The electromagnetic shielding effectiveness in the 30MHz to 1GHz frequency band is 65dB, which meets the anti-interference requirements of the weak current system in civil buildings; the rodent and ant gnawing test is carried out in accordance with GB / T2951.31-2008 standard, and the sheath has no gnawing damage after 180 days; during the production process, the extruded surface of the insulation layer is smooth, without air holes or pitting, and the production scrap rate is only 0.4%, which is far lower than the 12% of the existing technology.
[0045] Example 2: 5-core 70mm 2 Low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cables for underground utility tunnels 2.1 Cable structure design and parameter setting The cable in this embodiment is suitable for complex working conditions such as urban underground utility tunnels and other tunnels, where there is high current, high mechanical impact, and long-term immersion. It adopts a 5-core large cross-section structure to enhance insulation performance, mechanical protection performance, and waterproof performance. The structural parameters of each layer are as follows: (1) Pre-treated tin-plated copper conductive core wire: conductor cross-section 70mm² 2 It uses 37 strands of oxygen-free copper monofilament tightly twisted together, with a monofilament diameter of 1.5mm, a tin plating layer thickness of 1.0μm, and a composite coating thickness of 10μm to ensure the anti-oxidation performance and interfacial adhesion under high current operation. (2) Double-layer co-extruded composite cross-linked polyolefin insulation layer: total thickness 2.2mm, inner bonding transition layer thickness 0.3mm, outer main flame-retardant cross-linked insulation layer thickness 1.9mm, adaptable to high current carrying requirements and improves insulation withstand voltage performance; (3) Hollow foamed gradient flame retardant filling layer: foaming ratio 3.5 times, honeycomb hollow cell diameter 0.8mm, enhances heat insulation and buffer performance, and is suitable for high temperature and mechanical extrusion conditions in pipe gallery; (4) Composite shielding layer: Double copper tape wrapping with an overlap rate of 35%, and graphite conductive buffer composite tape with a thickness of 0.12mm, to improve electromagnetic shielding and heat dissipation performance and avoid excessive temperature rise of the cable core during high current operation; (5) Low-smoke halogen-free flame-retardant inner lining: 0.8mm thick, enhancing waterproof and isolation performance, suitable for long-term humid environment in pipe gallery; (6) Anti-corrosion buffer isolation non-woven fabric: weight 40g / ㎡, double-sided silicone-based lubricating anti-corrosion coating thickness 3μm, to enhance anti-corrosion and buffering effects; (7) Galvanized steel strip armored protective layer: 0.5mm thick, steel strip overlap width 4.0mm, to improve the resistance to extrusion and impact; (8) Rodent and ant repellent, weather-resistant, low-smoke, halogen-free outer sheath: 2.8 mm thick, 1.5 parts plant repellent extract, 0.8 parts ultraviolet light stabilizer, and 0.3 parts acid and alkali resistant modifier to adapt to the acid and alkali environment inside the pipe gallery.
[0046] 2.2 Raw material ratio (parts by weight) of the outer main flame-retardant cross-linked insulation layer EVA (30% VA content), 42 parts; LLDPE (melt index 1.8 g / 10 min), 22 parts; mPE (melt index 1.2 g / 10 min), 9 parts; silane crosslinking agent, 3.2 parts; organotin crosslinking catalyst, 0.6 parts; elastic core-shell compatibility toughening agent, 7 parts; three-phase composite flame-retardant filler, 52 parts; nano-boron nitride thermally conductive powder, 2.2 parts; composite antioxidant, 1.8 parts; composite lubrication processing aid, 1.6 parts. The proportion of the three-phase composite flame-retardant filler is the same as in Example 1, but the amount of nano-boron nitride added is appropriately increased to improve heat dissipation under high current operation.
[0047] 2.3 Adjustment of Key Parameters in Cable Manufacturing Process The manufacturing process in this embodiment is basically the same as that in Embodiment 1. However, the key process parameters have been adjusted to take into account the characteristics of large-section cables, as follows: (1) Conductor pretreatment: hot air drying temperature 60℃, drying time 40min, composite coating spraying pressure 0.4MPa, to ensure uniform coating on the surface of large cross-section conductors; (2) Mixing and granulation of insulating masterbatch: mixing temperature 145℃, mixing time 12min, ultrasonic dispersion time extended to 8min, twin-screw extruder screw speed 60r / min to ensure uniform dispersion of large amount of filler; masterbatch dried to moisture content 70ppm; (3) Double-layer co-extrusion composite insulation extrusion: die head temperature 145℃, extrusion speed 8m / min, segmented warm water pre-crosslinking total residence time 70s, to ensure sufficient pre-crosslinking of the thick insulation layer; (4) Cable forming process: The cable forming pitch is 20 times the outer diameter of the cable core, the cable forming speed is 4m / min, and the extrusion speed of the foam filler strip is simultaneously adjusted to 4m / min; (5) Secondary curing in warm water: curing temperature 78℃, curing time 17h, to ensure deep cross-linking of the large cross-section insulation layer, with a cross-linking degree of 87.8%.
[0048] 2.4 Finished Product Performance Testing and Result Analysis According to national standard testing, the finished cable in this embodiment meets all the performance requirements for use in underground utility tunnels. The core test results are as follows: (1) Flame retardant performance: Class A flame retardant, no flame propagation after 30 minutes of continuous fire supply, and no cable core breakdown; (2) Toxic properties of smoke: minimum light transmittance of smoke is 78%, halogen content is <0.05%, and toxicity level is t0. (3) Insulation performance: cross-linking degree 87.8%, after long-term heat aging at 90℃ for 1000h, tensile strength retention rate 86%, insulation resistance ≥8.0×10 13 Ω·m; (4) Mechanical and environmental performance: No cracks when bent at -40℃, the compressive strength of the armor layer is 22kN / m, the acid and alkali resistance test is immersion in 5% sulfuric acid solution for 72h, the sheath is free from corrosion and cracking; the rodent and ant gnawing test is free from damage after 180 days.
[0049] (5) Performance: The rated current carrying capacity is 240A. Under operation, the temperature rise of the cable core is only 45℃, which is far lower than the 56℃ of the existing technology, and it is suitable for the high current power supply requirements of the pipe gallery.
[0050] Example 3: 4-core 25mm 2 Low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable for rail transit 3.1 Cable structure design and parameter setting The cable in this embodiment is suitable for rail transit scenarios such as subways and light rails. It needs to have characteristics such as vibration resistance, high and low temperature resistance, and electromagnetic interference resistance. It adopts a 4-core structure, and the specific parameters are as follows: (1) Pre-treated tin-plated copper conductive core wire: conductor cross-section 25mm 2 24 strands of oxygen-free copper monofilaments are tightly twisted together, and the composite coating is 9μm thick; (2) Double-layer co-extruded composite cross-linked polyolefin insulation layer: total thickness 1.8mm, inner bonding transition layer thickness 0.25mm, outer main insulation layer thickness 1.55mm; (3) Hollow foam gradient flame retardant filling layer: foaming ratio 2.8 times, honeycomb hollow pore diameter 0.6 mm, to enhance vibration resistance and buffering performance; (4) Composite shielding layer: Double copper strip wrapping with an overlap rate of 32%, and graphite conductive buffer composite strip with a thickness of 0.11mm, which improves electromagnetic shielding effectiveness and avoids interference from weak electrical signals in rail transit; (5) Other structures: inner lining thickness 0.6mm, anti-corrosion buffer isolation non-woven fabric weight 35g / ㎡, armor layer thickness 0.4mm, outer sheath thickness 2.4mm, plant repellent extract added 1.3 parts.
[0051] 3.2 Raw material ratio (parts by weight) of the outer main flame-retardant cross-linked insulation layer 38 parts EVA, 26 parts LLDPE, 11 parts mPE, 2.8 parts silane crosslinking agent, 0.4 parts organotin crosslinking catalyst, 5.5 parts elastic core-shell compatibility toughening agent, 50 parts three-phase composite flame retardant filler, 2.0 parts nano boron nitride thermally conductive powder, 1.7 parts composite antioxidant, and 1.5 parts composite lubrication processing aid.
[0052] 3.3 Key parameters and performance testing of cable manufacturing process In the manufacturing process, the mixing temperature was 138℃ and the mixing time was 11 minutes; the double-layer co-extrusion die head temperature was 140℃, and the segmented warm water pre-crosslinking residence time was 55 seconds; the warm water secondary curing temperature was 72℃ and the duration was 14 hours. Testing showed that the finished cable had a crosslinking degree of 88.5%, an electromagnetic shielding effectiveness of 68 dB, and passed the vibration resistance test under the conditions of a frequency of 10 to 50 Hz, an amplitude of 0.5 mm, and a vibration duration of 100 hours. After the test, there was no structural loosening or insulation damage, and all performance characteristics met the standards for rail transit use.
[0053] Comparative Example: Commercially available conventional low-smoke halogen-free cables To highlight the technical advantages of this invention, a 3-core 10mm core of the same specification as in Example 1 was selected. 2 As a comparative example, a commercially available conventional low-smoke halogen-free cable was used, which did not adopt the 10 innovative features of this invention. The specific defects and test results are as follows.
[0054] (1) Structural defects: The conductor has no anti-oxidation composite coating and only uses ordinary tin plating; the insulation layer is a single-layer structure without an adhesive transition layer and uses a single aluminum hydroxide flame retardant filler; the filling layer is a solid flame retardant strip without a hollow foam structure; the shielding layer is a single-layer copper strip without a graphite buffer layer; there is no anti-corrosion buffer isolation non-woven fabric and the armor layer directly contacts the inner lining layer; the outer sheath has no plant repellent extract and only has basic flame retardant properties.
[0055] (2) Process defects: The traditional steam crosslinking process is adopted, with a crosslinking temperature of 120℃ and a duration of 24h, resulting in high energy consumption; the insulation material lacks a core-shell compatibilizer, and the filler is unevenly dispersed; the extrusion process lacks gradient cooling, and the sheath is prone to internal stress.
[0056] (3) Performance test results: The flame retardant rating is only Class C, and it will continue to burn after 10 minutes of continuous fire supply; the light transmittance of the combustion smoke is only 41%, the halogen content is 0.3%, and hydrogen chloride gas is released; the insulation cross-linking degree is only 63%, and it will become brittle after bending at -25℃; after 50 cycles of cold and heat, the insulation layer and conductor will delaminate; after 30 days of rodent gnawing test, the sheath will show obvious gnawing damage; during the production process, there are a lot of air holes and pitting on the extruded surface of the insulation layer, and the scrap rate is 12%; under high current operation, the cable core temperature rises by 54℃, which is much higher than the 45℃ of the embodiment of the present invention.
[0057] Through the comparison of the above three embodiments and comparative examples, it can be seen that the low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable proposed in this invention is significantly superior to the prior art in terms of fire safety, insulation performance, mechanical protection, processing performance, and environmental performance. Specifically, the conductor composite coating solves the oxidation and delamination problems; the core-shell compatibilizer and three-phase flame-retardant system improve the processing and flame-retardant properties of the insulation material; the hollow foam filling, composite shielding, and anti-corrosion isolation structures optimize the cable's heat insulation, anti-interference, and protective performance; the two-stage warm water cross-linking process reduces energy consumption and improves cross-linking uniformity; and the plant-repellent outer sheath achieves environmentally friendly rodent and ant repellency.
[0058] All finished cables in each embodiment meet the GB / T31247 Class A flame retardant standard, with smoke transmittance ≥78%, insulation cross-linking degree ≥87%, no cracks when bent at -40℃, and a production scrap rate ≤0.5%. They can be widely used in various high fire protection level and complex working conditions such as high-rise buildings, underground pipe corridors, rail transit, hospitals, and data centers, and have extremely high engineering application value and market promotion prospects.
[0059] It should be noted that the embodiments of the present invention are not limited to the above-described embodiments. Without departing from the core technical solution of the present invention, those skilled in the art can make reasonable adjustments to the raw material ratio, process parameters, and structural dimensions according to actual production needs. All improvements based on the innovative points of the present invention are within the protection scope of the present invention.
[0060] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0061] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A low-smoke, halogen-free, flame-retardant cross-linked polyolefin insulated cable and its preparation method, characterized in that: From the inside out, the following components are coaxially arranged: pre-treated tin-plated copper conductive core wire, double-layer co-extruded composite cross-linked polyolefin insulation layer, hollow foamed gradient flame-retardant filling layer, composite shielding layer, low-smoke halogen-free flame-retardant inner lining layer, anti-corrosion buffer isolation non-woven fabric, galvanized steel strip armored protective layer, and rodent-repellent, ant-resistant, weather-resistant, low-smoke halogen-free outer sheath layer. The surface of the pretreated tin-plated copper conductive core wire is sprayed with a composite coating of silane coupling agent and nano tin dioxide anti-oxidation. The double-layer co-extruded composite cross-linked polyolefin insulation layer comprises an inner bonding transition layer and an outer flame-retardant cross-linked insulation layer integrally extruded; the raw materials of the outer flame-retardant cross-linked insulation layer include, by weight: 35-45 parts of ethylene-vinyl acetate copolymer, 20-28 parts of linear low-density polyethylene, 8-12 parts of metallocene polyethylene, 2.2-3.5 parts of silane cross-linking agent, 0.3-0.8 parts of organotin cross-linking catalyst, 5-7 parts of elastic core-shell compatibility toughening agent, 40-55 parts of three-phase composite flame-retardant filler, 1.0-2.5 parts of nano boron nitride thermally conductive powder, 1.2-2.0 parts of composite antioxidant, and 1.0-1.8 parts of composite lubrication processing aid; The three-phase composite flame-retardant filler is a mixture of ultrafine aluminum hydroxide, nano magnesium hydroxide, zinc borate, expandable graphite, and melamine cyanurate in a mass ratio of 5:2:1:1:
1. The hollow foamed gradient flame-retardant filling layer is a cross-linked polyolefin foam strip with internal through-cell hollow honeycomb pores; the composite shielding layer is a double-layer staggered copper strip with a graphite conductive buffer composite strip wrapped longitudinally on the outside; the anti-corrosion buffer isolation non-woven fabric is a double-sided impregnated silicone-based lubricating anti-corrosion coating non-woven fabric; the rodent-repellent, ant-repellent, weather-resistant, low-smoke, halogen-free outer sheath is internally compounded with natural peppermint, capsaicin, camphor, and compounded plant repellent extracts.
2. The low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to claim 1, characterized in that, The conductive core wire is a multi-strand tin-plated oxygen-free copper tightly stranded conductor with a cross-section of 1.5-300mm². 2 A single cable consists of 2-5 insulated core wires twisted together; the composite coating on the conductor surface has a thickness of 5-12μm.
3. The low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to claim 1, characterized in that, The elastic core-shell compatibility toughening agent is a polyacrylate core-polyethylene shell structured nanoparticle with a particle size of 200-400nm; the nano-boron nitride thermally conductive powder constructs a continuous nano-thermal conductive network within the insulating layer.
4. The low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to claim 1, characterized in that, The hollow foamed flame-retardant filler strip has a foaming ratio of 2.5-3.5 times and a honeycomb hole diameter of 0.3-0.8 mm inside the filler strip; the double-layer copper strip wrapping overlap rate is ≥28%, and the overlap seams of the two layers of copper strips are staggered and have no shielding gaps.
5. A low-smoke, halogen-free, flame-retardant cross-linked polyolefin insulated cable according to claim 1, characterized in that, The galvanized steel strip armor thickness is 0.2-0.5mm, and the steel strip overlap width is ≥3mm; the total thickness of the double-layer composite insulation is 0.8-2.6mm, and the thickness of the low-smoke halogen-free flame-retardant outer sheath is 1.5-3.2mm.
6. The low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to claim 1, characterized in that, The finished cable has a flame retardant rating of GB / T31247A, a minimum light transmittance of ≥78% for combustion smoke, and a total halogen content of <0.05%; the insulation layer has a cross-linking degree of ≥88%, a long-term allowable operating temperature of 90℃, and no cracking or delamination when bent at -40℃; and an electromagnetic shielding effectiveness of ≥60dB in the 30MHz-1GHz frequency band.
7. The method for preparing a low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to any one of claims 1-6, characterized in that, Includes the following steps: S1: Conductor pretreatment; copper monofilament is drawn, hot-dip tin-plated, tightly stranded, dried with hot air at 50-60℃, then sprayed with a silane coupling agent + nano tin dioxide composite anti-oxidation coating, and air-dried naturally. S2: Ternary compound insulating masterbatch is mixed and granulated; all insulating raw materials are closed-loop mixing and ultrasonically dispersed into powder, twin-screw extrusion and water-cooled pelletizing, and the masterbatch is dried at 80℃ to a moisture content of ≤80ppm. S3: Double-layer co-extrusion composite insulation extrusion + segmented gradient warm water pre-crosslinking; the double-layer co-extrusion machine integrally extrudes the bonding transition layer and the flame-retardant insulation layer, and the semi-finished product is pre-crosslinked for 40-70 seconds in three-segment gradient warm water baths at 85℃, 90℃ and 95℃. S4: Cable forming + hollow foam filling synchronous extrusion; multiple insulated core wires are twisted into cables, and honeycomb hollow foam flame-retardant filler strips are extruded in a gap, and then wrapped with polyester tape for shaping. S5: Composite shielding and inner lining extrusion; double-layer staggered copper tape wrapping of the cable core + longitudinal wrapping of graphite buffer tape, followed by extrusion of low-smoke halogen-free flame-retardant inner lining layer; S6: Anti-corrosion buffer non-woven fabric wrapping + steel belt armor; the inner lining is wrapped with double-sided lubricated anti-corrosion isolation non-woven fabric on the outer side, and then galvanized steel belt is wrapped and armored at the gap. S7: Extrusion of rodent- and ant-repellent weather-resistant outer sheath; extrusion of armored cable core with outer sheath containing plant repellent extracts, three-stage gradient water cooling and shaping. S8: Constant temperature deep water secondary curing and deep cross-linking; the finished cable coil is immersed in a 70-80℃ constant temperature water bath for 12-18 hours to complete the deep cross-linking, and then air-dried, tested and put into storage. S3 and S8 together constitute a two-stage crosslinking process consisting of segmented gradient warm water pre-crosslinking and constant temperature deep water secondary curing.
8. The method for preparing a low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to claim 7, characterized in that: The S2 mixing temperature is 130-155℃, and the mixing time is 8-12 minutes; the temperature of each zone of the twin-screw extrusion is 120-145℃, and the nano boron nitride and elastic core-shell compatibilizer powder are simultaneously ultrasonically dispersed during the mixing process.
9. The method for preparing a low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to claim 7, characterized in that: S3 double-layer co-extrusion die head temperature 135-150℃; Step 5 inner liner extrusion temperature 125-140℃; S7 outer sheath extrusion temperature 130-148℃.
10. The method for preparing a low-smoke halogen-free flame-retardant cross-linked polyolefin insulated cable according to claim 7, characterized in that: The S7's three-stage gradient cooling water tank sequentially performs pre-cooling with 45℃ warm water, cooling with 25℃ ambient water, and low-temperature shaping at 10℃ to eliminate internal stress during the outer sheath molding process.